2019
DOI: 10.3168/jds.2019-16374
|View full text |Cite
|
Sign up to set email alerts
|

Altering the ratio of dietary C16:0 and cis-9 C18:1 interacts with production level in dairy cows: Effects on production responses and energy partitioning

Abstract: The objective of our study was to evaluate the effects of altering the dietary ratio of palmitic (C16:0) and oleic (cis-9 C18:1) acids on nutrient digestibility, energy partitioning, and production responses of lactating dairy cows. Cows were blocked by milk yield and assigned to 3 groups (12 cows per group) in a main plot: low (45.2 ± 1.7 kg/d), medium (53.0 ± 1.6 kg/d), and high (60.0 ± 1.9 kg/d). Within each production group, a truncated Latin square arrangement of fatty acid (FA) treatments was used in 2 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 47 publications
0
24
3
Order By: Relevance
“…An increase in dietary content of cis-9 C18:1 with increasing HFM (0.85, 0.90, 0.95, and 1.01% of DM for 0HFM, 3.3HFM, 6.7MFM, and 10HFM, respectively) may have increased fatty acid digestibility. de Souza et al (2019) reported that increasing cis-9 C18:1 from 0.68 to 0.98% of diet DM linearly increased digestibility of total, 16-C, and 18-C fatty acids.…”
Section: Nutrient Digestibility and Nitrogen Utilizationmentioning
confidence: 99%
“…An increase in dietary content of cis-9 C18:1 with increasing HFM (0.85, 0.90, 0.95, and 1.01% of DM for 0HFM, 3.3HFM, 6.7MFM, and 10HFM, respectively) may have increased fatty acid digestibility. de Souza et al (2019) reported that increasing cis-9 C18:1 from 0.68 to 0.98% of diet DM linearly increased digestibility of total, 16-C, and 18-C fatty acids.…”
Section: Nutrient Digestibility and Nitrogen Utilizationmentioning
confidence: 99%
“…Characterization and FA profiles of the supplements are shown in Table 1. Truncated Latin square designs have been used previously in experiments in dairy science (Clark and Armentano, 1999;Weiss et al, 2013;de Souza et al, 2019a). For our truncated Latin square design with 3 × 2 treatments and periods, multiples of 12 cows were required to balance treatment sequences; therefore, each cow was assigned to 2 treatments in 2 different periods.…”
Section: Design and Treatmentsmentioning
confidence: 99%
“…Research has examined the effects of feeding FA to dairy cows and differences have been reported depending on the feeding rate, production level, and FA profile (Rabiee et al, 2012). We have recently carried out research with blends of FA using commercial supplements (de Souza et al, , 2019a, but research comparing commercially available FA supplements containing different amounts of C16:0 and C18:0 is limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In post-peak cows, we recently observed that feeding a FA blend with a high content of C16:0 (80% C16:0) increased milk energy output and energy partitioning toward milk, whereas feeding a FA blend with a combination of C16:0 and cis-9 C18:1 (45% C16:0 and 35% cis-9 C18:1) increased energy allocated to BW and the partitioning of energy to BW compared with a non-fat-supplemented diet (de Souza et al, 2018). Interestingly, feeding cis-9 C18:1 not only increased BW gain in post-peak cows but also plasma insulin compared with non-FA-supplemented control diets and other FA supplements (de Souza et al, 2018(de Souza et al, , 2019. Altogether, these results suggest that C16:0 and cis-9 C18:1 are able to alter nutrient partitioning between the mammary gland and adipose tissue, which may allow for different FA supplements to be used in different situations according to the metabolic priority of dairy cows and management needs.…”
Section: Introductionmentioning
confidence: 99%